Penerapan Model Pembelajaran Problem Based Learning disertai Media Video terhadap Hasil Belajar Biologi pada Ranah Sikap Peserta Didik Kelas X SMA Negeri 1 Sitiung - AULIA AFZA; Elsa Feronika Yulianto (Fakultas Tarbiyah dan Ilmu Keguruan, Institut Agama Islam Negeri Kerinci, 2020)
This research is motivated by student pay less attention when the teacher delivers the material, lack of reading learning resources, and lack of activities working together in groups, such as give opinion in groups and do assignment in groups. This shows that the competence of studen’s attitude is still low. In addition, teachers have not used the right models and media. The research population was all students of class X SMA N 1 Sitiung. The sampling technique was purposive sampling. The research design used Randomized d Group Posstest Only Design. The research instrument was an observation sheet of student’s attitudes with indicators of responsibility and cooperaton in groups. Data analysis used t test. Based on the value of learning outcomes in the domain of student’s attitude, it was found that th = 2.39 while tt = 1.67 mean that th > tt and hypotesis was accepted. It can be concluded that Problem Based Learning model with video can improve learning outcomes in the domain of student’s attitude class X SMA N 1 Sitiung.